2015
DOI: 10.1210/jc.2014-3556
|View full text |Cite
|
Sign up to set email alerts
|

PAPSS2 Deficiency Causes Androgen Excess via Impaired DHEA Sulfation—In Vitro and in Vivo Studies in a Family Harboring Two Novel PAPSS2 Mutations

Abstract: Context:PAPSS2 (PAPS synthase 2) provides the universal sulfate donor PAPS (3′-phospho-adenosine-5′-phosphosulfate) to all human sulfotransferases, including SULT2A1, responsible for sulfation of the crucial androgen precursor dehydroepiandrosterone (DHEA). Impaired DHEA sulfation is thought to increase the conversion of DHEA toward active androgens, a proposition supported by the previous report of a girl with inactivating PAPSS2 mutations who presented with low serum DHEA sulfate and androgen excess, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…MTHFD2 is likely responsible for mitochondrial production of both NADH and NADPH in rapidly proliferating cells [41]. PAPSS2 gene plays an important role in modulating ovarian function and female fertility by control of the bioavailability of ovarian androgen [42]. Adrenodoxin, a versatile ferredoxin, is involved in steroid hormone biosynthesis and vitamin D and bile acid metabolism [43].…”
Section: Discussionmentioning
confidence: 99%
“…MTHFD2 is likely responsible for mitochondrial production of both NADH and NADPH in rapidly proliferating cells [41]. PAPSS2 gene plays an important role in modulating ovarian function and female fertility by control of the bioavailability of ovarian androgen [42]. Adrenodoxin, a versatile ferredoxin, is involved in steroid hormone biosynthesis and vitamin D and bile acid metabolism [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this premature onset of joint degeneration is due to impaired proteoglycan sulfation. Inactivating mutations in PAPSS2 have also been linked to andrenocortical androgen excess and premature pubarche due to impaired dehydroepiandrosterone (DHEA) sulfation (24,25). DHEA sulfate is believed to be a critical hormone with a myriad of anti-aging effects (26).…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, a number of PAPSS2 mutations have been reported in patients with SEMD/brachyolmia, with only very limited data on endocrine function [137-139]. Steroid metabolome profiling following an oral DHEA challenge, performed in a family with 2 brothers affected by PAPSS2 deficiency, revealed that also the mother, a heterozygous carrier of a severe loss-of-function mutation, had impaired DHEA sulfation with clinical and biochemical evidence of androgen excess [140]. …”
Section: Monogenic Disorders Of Adrenal Steroidogenesismentioning
confidence: 99%